The Mediating Impact of Islamic Lifestyle and Religion Perceived Behavior Control on the Infulence of Income and Consumer Behavior Among Muslimah Career - Tyas Ayuningrum; Faqih Nabhan (Al-Amwal : Jurnal Ekonomi dan Perbankan Syari'ah, 2024)
The purpose of this study was to determine how good the effect of income on consumptive behavior with Islamic lifestyle and religious perceived behavior control as intervening variables for career Muslim women in Salatiga city. The type of research used is quantitative research with data collection by distributing questionnaires using an interval scale (1-10) with a population of Salatiga career Muslim women. The sample taken was 100 respondents using the Purposive Sampling technique. The analysis technique in this study uses Structural Equation Modeling (SEM) with Partial Least Square (PLS) technique, while the analytical tool used in this study is the SmartPLS 4.0 program. The results of this study indicate that: (1) Income has a Positive and Significant Effect on Islamic Lifestyle. (2) Income has a Positive and Significant Effect on Religious Perceived Behavior Control. (3) Income has a Negative and Insignificant Effect on Consumptive Behavior. (4) Islamic Lifestyle has a Negative and Significant Effect on Consumptive Behavior. (5) Religious Perceived Behavior Control Negatively and Significantly Affects Consumptive Behavior. (6) Income has a Significant Negative Effect on Consumptive Behavior with Islamic Lifestyle as an intervening variable. (7) Income has a Significant Negative Effect on Consumptive Behavior with Religious Perceived Behavior Control as an intervening variable.Keywords: Consumptive Behavior, Income, Islamic Lifestyle and Religious Percheived Behavior Control